Design of an Information System for Management of Organic Waste Bins As a Processor for Fertilizing Compost for Family Medicinal Plants - Salsabila Andriputri, Syifa; Supriyati, S; Putri, Pritha Andriana; Alifah, Tsara Noor; Azzahra, Almira Fathriana; Rahayu, Syifa Siti; Bahri, Ramadhan Syaeful (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2023)
During global climate change and the threat of environmental pollution, society is increasingly aware of the crucial role played by nature conservation and waste management. One of the big challenges in this context is waste management, especially organic waste. This research uses a method with a qualitative research approach. Qualitative data collection techniques were carried out using interviews and observations to explore the problems faced. The approach used in this research is experimental research. The data collected is managed to create a design for a website-based information system that is used to provide various information and guidelines for managing organic waste bins. This website was designed with the aim of deepening understanding of the problems faced by the community regarding organic waste management and the use of organic waste bins. The research results provide an overview of the design of an information system that can be used for various activities related to managing organic waste bins. This website was designed with the aim of deepening understanding of the problems faced by the community regarding organic waste management and the use of organic waste bins. It is hoped that these results can be translated into a system that can provide significant support for organic waste management in the community so that the impact can be felt directly in the community with a healthier and more comfortable environment.